Treatment of bilateral femoral fractures with external fixing devices - Janbakhishov, Galandar; Akberov, Shahin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article describes experience of treatment of 20 patients having bilateral fractures of their lower extremities with rod and pin-rod external fixing devices. Within 3 years of follow-up, excellent results were achieved in 16 cases, good in 3, and satisfactory in 1. The use of a rod device for bilateral fractures of the femur in its upper and middle one-third part turned out to be the most optimum.